THE IMPACT OF 2018 EARTH TREMORS ON GROUNDWATER QUALITY IN THE FEDERAL CAPITAL TERRITORY, ABUJA - Ezisi, Ogugua P.; Mmonwuba, C. N.; Ezugwu, N. C.; Mmonwuba, C. N. (FUDMA Journal of Sciences, 2024)
The impact of 2018 earth tremors on groundwater quality in the Federal Capital Territory, Abuja. Twenty water samples were collected from five locations within the study area: Mpape, Maitama, Gwarinpa, Jahi, Wuse. The methods used in the study included data collection, and data analysis. One and a half EVA cans were used to collect each water sample, ensuring that the equipment was sterilized and samples were properly preserved for analysis. Seismographs were used to measure and record the earthquakes that occurred in 2018. The results showed heavy metal concentrations of Pb (0.013 – 0.050 mg/l; WHO limit 0.01 mg/l), Cd (0.113 – 0.170 mg/l; WHO limit 0.003 mg/l), Hg (0.001 – 0.609 mg/l; WHO limit 0.006 mg/l), Cr (0.001 – 0.065 mg/l; WHO limit 0.05 mg/l), and As (0.016 – 0.064 mg/l; WHO limit 0.01 mg/l respectively, which are slightly higher than the permissible limits set by WHO. Drinking from these water sources poses significant health risks to the people in the study areas. However, the study helps to identify potential high-risk areas and their likely impact on water quality parameters. The findings will support the development of response and mitigation strategies to protect groundwater resources from contamination caused by seismic activity. In conclusion, the concentrations of heavy metals exceeded the limit approved by WHO.